Work environments and back pain among nurses in Hospital Universiti Sains Malaysia - Samsudin, Suhaimi (2013)
Introduction Profession as a nurse needs dedication and patience to endure all the challenges. This profession exposes them to many occupational hazards including biological, chemical, physical, ergonomic and psychosocial. In this study, the general aim is to determine prevalence of back pain and also association of work environments toward back pain among nurses in Hospital Universiti Sains Malaysia (HUSM) Kubang Kerian, Kelantan, Malaysia. Methods This was a cross sectional study involved 130 nurses from wards and clinics in Hospital Universiti Sains Malaysia which was conducted from September 2012 till May 2013. All respondents were chosen through simple random sampling from ward and clinic nurses lists. Validated English version and Malay translation of Modified Nordic Musculoskeletal Questionnaire and Roland Morris Disability Questionnaire for back pain characteristics and severity were used in this study. Prevalence of back pain was determined with its 95% CI while associated factors and its relation with back pain was analyzed using multiple logistic regression analysis. Results Out of 130 respondents, majority were Malays (90.8%) and females (94.6%). Age of respondents ranged from 23 to 58 years old with mean of 41.5(SD=10.56) years old. Prevalence of nurses having back pain in life for this study was 71.6% (95% CI: 61.1,82.1) with low back pain type was the highest among all back pain (48.6%, 95% CI: 37.0,63.1). From multivariate analysis using multiple logistic regression, significant associated factors for back pain after controlling for potential confounders were total household income (OR: 3.54, 95% CI 1.23,10.15, p=0.019) and BMI (OR: 4.47, 95% CI 1.55,12.86, p=0.005). Conclusion Prevalence of back pain among nurses in HUSM is high, corresponds with other studies in Malaysia and South East Asia. In this study, significant associated risk factors are total household income and BMI.